Dance Learning Model Using Stories in Elementary Schools - Yuliasma; Nerosti; Afifah Asriati; Desfiarni (Universitas Pendidikan Ganesha, 2023)
Dance learning in elementary schools is starting to be neglected, there are even schools that don't teach dance, especially in the form of practice. This is because the teacher has difficulty choosing a dance learning model that is systematic and easy to use. The purpose of this study was to analyses the validity, practicality and effectiveness of the TAGUNTA learning model (Dance using Stories) in Elementary Schools. This research is a type of development research (Research and Development). Following the product development steps proposed by Borg & Gall. Research data collection techniques and instruments in the form of qualitative and quantitative data consisting of preliminary study data, validity test, practicality test and product effectiveness test. To see the feasibility of the model, validity tests were carried out by four experts, practicality tests by teachers and students and effectiveness tests through student learning outcomes tests. The results of this study indicate that the TAGUNTA Learning Model in Elementary Schools that the researchers developed has been tested to be able to overcome the problems of learning dance in elementary schools. The feasibility of the TAGUNTA learning model is evidenced by the results of the validity test with an overall average score in the very valid category, a practicality test with an overall average score in the practical category, and an effectiveness test with an overall average score in the category very effective. Thus, it can be concluded that the TAGUNTA Learning Model that the researchers developed is valid, practical, effective, and appropriate for use in teaching dance in elementary schools.